Phosphorus nutrition of woody plants: many questions – few answers. (31st July 2013) - Rennenberg, H.; Herschbach, C.; Hawkesford, M.
Abstract Phosphorus (P) acquisition, cycling and use efficiency has been investigated intensively with herbaceous plants. It is known that local as well as systemic signalling contributes to the control of P acquisition. Woody plants are long‐lived organisms that adapt their life cycle to the changing environment during their annual growth cycle. Little is known about P acquisition and P cycling in perennial plants, especially regarding storage and mobilisation, its control by systemic and environmental factors, and its interaction with the largely closed ecosystem‐level P cycle. The present report presents a view on open questions on plant internal P cycling in woody plants.